Pengaruh Profitabilitas Dan Leverage Terhadap Manajemen Laba Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode Tahun 2019-2022 - Hamdana; Hermawati Samsudin (JURNAL SeMaRaK, 2024)
This study aims to determine the effect of profitability and leverage on earnings management in miningsector companies listed on the Indonesia Stock Exchange. The sample in this study is 72 mining sectorcompanies listed on the Indonesia Stock Exchange in the 2019-2022 period. The sample selection used apurposive sampling technique. The data used is secondary data obtained from the company's financialstatements. To measure profitability using Return on Assets (ROA), to measure leverage using the Debtto-Equity Ratio (DER). To measure earnings management using discretionary accrual (DA). The researchmethod used in this research is descriptive statistical method. Multiple linear regression and correlationanalysis. Based on the research results, the profitability variable has a positive and significant effect onearnings management in mining sector companies listed on the IDX. The leverage variable also has apositive and significant effect on earnings management of mining sector companies listed on the IDX. Andsimultaneously profitability and leverage together have a significant positive influence on the earningsmanagement of mining sector companies listed on the IDX.Keywords: Debt to Assets Ratio, Earnings management, Leverage, Profitability, ROA